Bulk Transport Vehicle Fire Safety: Preventing a Mine Site Disaster - Harry Verakis; Thomas Lobb (International Society of Explosives Engineers, 2008)
Widespread use of ammonium nitrate compositions for mine blasting operations has led to various bulk transport vehicles designed especially for the explosives industry over the past half century or more. The advancements in explosives technology and continuing developments in bulk transportation have resulted in a variety of blasting agents and, more recently, oxidizers being transported and used from specially designed bulk transport vehicles. It is estimated that about 2000 bulk transport vehicles are used in mining operations. Many of the bulk vehicles carry about 15,000 to 33,000 pounds (6808 to 14,968 kilograms) of payload and some can carry up to 50,000 pounds (22,679 kilograms) for large open cast mines. Thus, it is imperative that detailed knowledge and safety instructions are available from the blasting personnel and mine management should an unplanned incident such as a fire occur with a bulk transport vehicle at a mine site.